An Analysis of theNinth Grade English Test Questions Based on the Revised Edition of Bloom’s Taxonomy - Ria Saraswati (Universitas Bunda Mulia, 2017)
This study aimed at identifying and analyzing the types and levels of questions available in the ninth grade English language test which are used in Junior High School in Depok during the academic year 2012-2013.The purpose of the analysis was to determine the distribution of the questions over the six levels of the new version of Bloom's Taxonomy of the cognitive domain. A classroom test does not focus only on students’ knowledge or problems with the language, but furthermore, it is concerned with evaluation for the purpose of enabling teachers to increase their own effectiveness by making adjustment in their teaching. The sample of the study consisted of the Ninth grade English language test where the researcher analyzed 50 questions. A study analysis sheet was prepared and used in the classification of the questions according to the new version of Bloom's Taxonomy to achieve the purposes of the study. The results show that understanding the levels of questions is necessary. They lead the students to have deep understanding toward the questions presented, so that in answering the questions, they will become easier to answer. In light of the results, the researcher recommended to improve the questions in the English test to cover the six levels of the new version of Bloom's Taxonomy and to train teachers and designers of curriculum to use and write questions following the new version of Bloom's Taxonomy. Keywords: ninth grade, new version of Bloom's Taxonomy, English language test